Differential diagnosis of myelofibrosis based on WHO 2008 criteria: Acute panmyelosis with myelofibrosis, acute megakaryoblastic leukemia with myelofibrosis, primary myelofibrosis and myelodysplastic syndrome with myelofibrosis. Issue 6 (22nd May 2013) - Bae, E.; Park, C.‐J.; Cho, Y.‐U.; Seo, E.‐J.; Chi, H.‐S.; Jang, S.; Lee, K.‐H.; Lee, J.‐H.; Lee, J.‐H.; Suh, J.‐J.; IM, H.‐J.
Summary Introduction The aim of this study was to characterize clinicopathological features of acute panmyelosis with myelofibrosis (APMF), acute megakaryoblastic leukemia with myelofibrosis (AMKL‐MF), primary myelofibrosis (PMF) and myelodysplastic syndrome with myelofibrosis (MDS‐MF) in order to provide the keys to the differential diagnosis of bone marrow (BM) fibrosis. Methods We compared age, gender, splenomegaly, serum lactate dehydrogenase level, blood cell counts, blast counts in peripheral blood (PB) and BM, megakaryocyte counts, BM cellularity, dysplasia, and the karyotypes of patients with APMF (n = 6), AMKL‐MF (n = 7), PMF (n = 44), and MDS‐MF (n = 44). Results APMF showed hyperplasia of all three lineages, increase in megakaryocyte count with dysplasia and frequent abnormal karyotypes. AMKL‐MF was associated with elevated BM blast counts, decreased BM megakaryocyte count with rare megakaryocytic dysplasia and chromosome 21 abnormality. PMF patients displayed splenomegaly, rare blasts in PB/BM, and JAK2 V617F mutation. MDS‐MF patients showed pancytopenia, dysplasia in all three lineages and recurrent chromosomal abnormalities involving chromosome 5, 7, 12, and 17. Conclusions Although differential diagnosis among APMF, AMKL‐MF, PMF, and MDS‐MF is very challenging due to the overlapping clinical and morphological features, meticulous investigation of the patient with respect to splenomegaly, blood cell count, PB and BM findings, and karyotype will serve as a guide to correct diagnosis.